2011
DOI: 10.1523/jneurosci.0595-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Rules Ventral Prefrontal Cortical Axons Use to Reach Their Targets: Implications for Diffusion Tensor Imaging Tractography and Deep Brain Stimulation for Psychiatric Illness

Abstract: The ventral prefrontal cortex (vPFC) is involved in reinforcement-based learning and is associated with depression, obsessive-compulsive disorder, and addiction. Neuroimaging is increasingly used to develop models of vPFC connections, to examine white matter (WM) integrity, and to target surgical interventions, including deep brain stimulation. We used primate (Macaca nemestrina/Macaca fascicularis) tracing studies and 3D reconstructions of WM tracts to delineate the rules vPFC projections follow to reach thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
181
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(196 citation statements)
references
References 38 publications
11
181
1
1
Order By: Relevance
“…In terms of mechanisms data published to date suggest that a DBS-induced modulation of fiber pathways might play a role in the antidepressant-like effects of stimulation in humans (62). Preclinical studies are consistent with these findings but also show that a functional target inactivation might be important.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In terms of mechanisms data published to date suggest that a DBS-induced modulation of fiber pathways might play a role in the antidepressant-like effects of stimulation in humans (62). Preclinical studies are consistent with these findings but also show that a functional target inactivation might be important.…”
Section: Discussionmentioning
confidence: 56%
“…This has been shown to influence activity in brain regions at a distance from the stimulated target, leading to neurotransmitter release and inducing plastic changes in systems and substrates thought to be involved in the mechanisms of antidepressant treatments (56,57). In a recent study, the trajectory of white matter tracts running from prefrontal/orbitofrontal cortical regions to subcortical structures has been characterized in nonhuman primates with the use of tract tracing techniques (62). A functional organization of components from medial to lateral areas in the PFC and orbitofrontal cortex has been identified in tracts such as the uncinate fascicle and the internal capsule.…”
Section: Mechanisms Involved In the Effects Of Vmpfc Stimulation In Tmentioning
confidence: 99%
“…There is a high degree of homology of fear circuits in rodents and humans, especially in the prefrontal cortex and amygdala (13,(54)(55)(56)(57). Fibers from the ventromedial prefrontal cortex (a homolog of IL) and the dorsal anterior cingulate cortex (a homolog of PL) pass through the VS and ventral capsule on their way to the amygdala and thalamus (15). Clinical DBS of the VC/VS site shows a similar dorsalventral pattern to what we observed here: stimulation ventral to the most clinically effective site can induce panic and fear (58,59).…”
Section: Discussionmentioning
confidence: 99%
“…The DBS target for OCD is the VC/VS (14), which contains fiber bundles interconnecting cortical areas implicated in fear extinction, such as the ventromedial prefrontal cortex, the dorsal anterior cingulate cortex, and the orbitofrontal cortex (OFC), with subcortical areas implicated in conditioned fear, such as the amygdala (15). Previous studies in anesthetized rats (16,17) have shown that DBS of the VS modifies the excitability of the OFC as well as prelimbic (PL) and infralimbic (IL) prefrontal regions that modulate fear via projections to the amygdala (18).…”
Section: Eep Brain Stimulation (Dbs) Is a Neurosurgical Techniquementioning
confidence: 99%
“…Moreover, neurosurgical interventions (lesions or deep brain stimulation-DBS) within the ventral internal capsule (VC), ventral striatum (VS), or dACC (treatments for intractable OCD) all act on subcomponents of the vmPFC/OFC/dACC-basal ganglia network (Greenberg et al, 2010). Indeed, DBS interventions specifically affect vmPFC, OFC, and possibly dACC connections with striatum, thalamus, and/or brainstem (Figure 1) (Lehman et al, 2011). The efficacy of VC/VS DBS (or lesions) for OCD likely requires modulating the OFC/ vmPFC/dACC-basal ganglia circuit.…”
mentioning
confidence: 99%